Pemberdayaan Lembaga Pemerintahan Nagari di Nagari Kacang Kabupaten Solok dengan Menggunakan Konsep Dynamic Governance - Alfidina Kennedy; Karjuni Dt. Maani (Jurusan Ilmu Administrasi Negara, 2022)
This research is motivated by the lack of quality performance of the nagari government apparatus in terms of services provided to the community due to the weak ability of the nagari apparatus in understanding their main duties and functions. Therefore, empowerment activities are needed to increase the capacity of the nagari government apparatus. The purpose of this study is to describe the form of empowerment of nagari government institutions in Nagari Kacang, Solok Regency by using the concept of dynamic governance, to identify obstacles in empowering nagari government institutions in Nagari Kacang, Solok Regency by using the concept of dynamic governance. This study uses a qualitative approach with a descriptive method, this research was carried out at the Wali Nagari Kacang Office, Solok Regency. The data collection techniques used were observation, interviews and documentation studies. The findings of the research show that the empowerment of nagari government institutions in Nagari Kacang, Solok Regency by using the concept of dynamic governance can be said to have not been successful because it is only done once a year and there are still undisciplined nagari government officials. In its implementation, there are still obstacles faced by the Office of the Wali Nagari Kacang and the Community and Nagari Empowerment Service of Solok Regency.